Non-Tracing Cases: Tracing their Mistake - Biebel, Nathan (Journal of moral philosophy, 2025)
When is ignorance culpable? One plausible suggestion is that culpable ignorance is always a form of derivative responsibility. One is culpable on accounts like this, only when one’s ignorance can be traced back to some past bit of behavior for which the agent was directly (non-derivatively) responsible, and which led to unwitting wrongdoing. One of the main arguments against these so-called tracing accounts claims that our practices include many cases wherein we judge an ignorant agent blameworthy even though there is nothing to which we can plausibly trace her culpability. This article defends tracing accounts from these alleged non-tracing cases. I argue that, when we adequately highlight or fill in the details of each case then either no tracing explanation is needed because it is a case of direct, non-derivative responsibility, there is a tracing explanation after all, or we don’t judge the agent blameworthy.